PULSE CHARACTERISTICS OF NETWORK SATELLITE SYSTEMS ADAPTIVE ANTENNA FOR ASSESSING CORRELATION INTERFERENCE MATRIX - Kharchenko, Volodymyr; Shvets, Valeriyan (Proceedings of National Aviation University (archive), 2017)
Purpose: On the basis of spatial filtering, we propose a method for direct calculation of the inverse correlation interference matrix with unknown parameters of the input action for controlling the pattern of the adaptive antenna array using the impulse response of the spatial filter. Methods: the approach is based on the theory of random processes and adaptive signal processing. Results: the proposed method of direct calculation of the inverse correlation matrix has shown the possibility of carrying out such calculations without a prior knowledge of the interference direction, the correlation function of the interference, and also the spectral characteristics of the interference. The method allows to reduce the calculation time of the inverse correlation matrix and eliminate the errors caused by constructive inaccuracies of the radio channels of the adaptive antenna array, which in turn reduces the error in measuring the direction of the interference source. Discussion: the method is suggested in order to ensure availability and consistency of network satellite systems’ navigation data.